Association between regulator inspection and ratings on primary care prescribing: an observational study in England 2014 to 2019 - Thomas Allen; Kieran Walshe; Nathan Proudlove; Matt Sutton (BMC, 2024)
Abstract Background Healthcare regulators in many countries undertake inspections of healthcare providers and publish inspection outcomes with the intention of improving quality of care. Comprehensive inspections of general practices in England by the Care Quality Commission began for the first time in 2014. It is assumed that inspection and rating will raise standards and improve care, but the presence and extent of any improvements is unknown. We aim to determine if practice inspection ratings are associated with past performance on prescribing indicators and if prescribing behaviour changes following inspection. Methods Longitudinal study using a dataset of 6771 general practices in England. Practice inspection date and score was linked with monthly practice-level data on prescribing indicators relating to antibiotics, hypnotics and non-steroidal anti-inflammatory drugs. The sample covers practices receiving their first inspection between September 2014 and December 2018. Regression analysis and the differential timing of inspections is used to identify the impact on prescribing. Results Better-rated practices had better prescribing in the period before inspections began. In the six months following inspections, no overall change in prescribing was observed. However, the differences between the best and worse rated practices were reduced but not fully. The same is also true when taking a longer-term view. There is little evidence that practices responded in anticipation of inspection or reacted differently once the ratings were made public. Conclusion While some of the observed historic variation in prescribing behaviour has been lessened by the process of inspection and ratings, we find this change is small and appears to come from both improvements among lower-rated practices and deteriorations among higher-rated practices. While inspection and rating no doubt had other impacts, these prescribing indicators were largely unchanged.